A promising metabolite, 9-aminominocycline, restores the sensitivity of tigecycline against tet(X4)-positive Escherichia coli - Sun, Feifei; Zhang, Lin; Ma, Xuan; Ali, Tariq; Wu, Yongning; Li, Lin (Frontiers in Microbiology, 2024)
The emergence and widespread of tigecycline resistance undoubtedly poses a serious threat to public health globally. The exploration of combination therapies has become preferred antibacterial strategies to alleviate this global burden. In this study, tigecycline-resistant tet(X4)-positive Escherichia coli were selected for adjuvant screening. Interestingly, 9-aminominocycline (9-AMC), one of the tigecycline metabolites, exhibits synergistic antibacterial activity with tigecycline using checkerboard assay. The efficacy in vitro and in vivo was evaluated, and the synergistic mechanism was further explored. The results suggested that 9-AMC combined with tigecycline could inhibit the growth of antibiotic resistant bacteria, efficiently retard the evolution of tet(X4) gene and narrow the drug mutant selection window. In addition, the combination of tigecycline and 9-AMC could destroy the normal membrane structure of bacteria, inhibit the formation of biofilm, remarkably reduce the level of intracellular ATP level, and accelerate the oxidative damage of bacteria. Furthermore, 9-AMC is more stable in the bind of Tet(X4) inactivating enzyme. The transcriptomics analysis revealed that the genes related to the 9-AMC and tigecycline were mainly enriched in ABC transporters. Collectively, the results reveal the potentiation effects on tigecycline and the probability of 9-AMC as a novel tigecycline adjuvant against tet(X4)-positive Escherichia coli, which provides new insights for adjuvant screening.